Russia in the 21st century : the prodigal superpower - Rosefielde, Steven (Cambridge, UK ; New York : Cambridge University Press, 2004)
This book demonstrates Russia's intention to re-emerge as a full-fledged superpower before 2010 that would challenge America and China and potentially threaten a new arms race. Contrary to conventional wisdom, this goal is within the Kremlin's grasp, but the cost to the Russian people and global security would be immense.
Cover; Half-title; Title; Copyright; Dedication; CONTENTS; FIGURES AND TABLES; ACRONYMS; PREFACE; ACKNOWLEDGMENTS; INTRODUCTION; 1 AFTER "THE END OF HISTORY"; 2 PRODIGAL SUPERPOWER; 3 STRUCTURAL MILITARIZATION; 4 WHAT COULD HAVE BEEN DONE?; 5 MUSCOVITE METAMORPHOSIS; 6 MILITARY-INDUSTRIAL REFORM; 7 NATIONAL VULNERABILITIES; 8 THE MIASMA OF GLOBAL ENGAGEMENT; 9 PUTIN'S CHOICE; 10 CANDOR; CONCLUSION; GLOSSARY; NOTES; SELECTED BIBLIOGRAPHY; INDEX.
Includes bibliographical references (pages 147-234) and index.
Print version record.
eBooks on EBSCOhost
Keywords: National security -- Economic aspects -- Russia (Federation); Military-industrial complex -- Russia (Federation); Security, International; Russia (Federation) -- Military policy; Complexes militaro-industriels -- Russie; BUSINESS & ECONOMICS -- Industries -- Service; Military-industrial complex; Military policy; National security -- Economic aspects; Security, International; Russia (Federation); Electronic books; Electronic books